(untitled) (Journal of the College of Basic Education, 2022)
In this paper, the Bernstein Polynomial method is used to find an approximate solution initials values problem for high-order nonlinear Volterra Fredholm integro differential equation of the second kind. Some different examples considered and the solution discussed numerically and display graphically. By enhancing the degree of Bernstein Polynomial, we can improve the accuracy results. The simulation results were also compared with other researchers’ work.